2021
DOI: 10.1051/e3sconf/202125501037
|View full text |Cite
|
Sign up to set email alerts
|

Green human resource management: how to implement environmental issues into HR practices

Abstract: The purpose of study is to analyze the spread of practices of GHRM in Ukraine and develop conceptual basis for the implementation of environmental issues into HR practices. The paper focuses on the providing integrated approach to GHRM practices, which should be implemented in all HRM functions. The article contains important theoretical and methodological principles for research of GHRM. The research showed that the GHRM could be seen as a tool for implementing corporate social responsibility programs related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…SD offers a new way of thinking about and managing human impacts, creating longerlasting positive outcomes for more significant benefits to human societies (economic, human, social, and ecological), ensuring long-term resource availability and quality. Along these lines, Unsworth et al (2021) posit that employees' green behavior contributes to environmental sustainability (Malik et al, 2021), which agrees with Tsymbaliuk et al (2021) when they argue that green human resource management practices should be implemented across all human resource management functions: organizational design and workforce planning, job analysis and design, recruitment, onboarding and matching, human resource accounting, performance appraisal and management, training and professional development, corporate culture, compensation and benefits, and employee relations.…”
Section: Internal Social Responsibilitymentioning
confidence: 73%
“…SD offers a new way of thinking about and managing human impacts, creating longerlasting positive outcomes for more significant benefits to human societies (economic, human, social, and ecological), ensuring long-term resource availability and quality. Along these lines, Unsworth et al (2021) posit that employees' green behavior contributes to environmental sustainability (Malik et al, 2021), which agrees with Tsymbaliuk et al (2021) when they argue that green human resource management practices should be implemented across all human resource management functions: organizational design and workforce planning, job analysis and design, recruitment, onboarding and matching, human resource accounting, performance appraisal and management, training and professional development, corporate culture, compensation and benefits, and employee relations.…”
Section: Internal Social Responsibilitymentioning
confidence: 73%
“…Moreover, In Egypt, Farid [60] found that HR managers in hotels were aware enough and familiar with the GHRM concept. While Tsymbaliuk et al [66] found that GHRM practices have not become widespread in Ukraine.…”
Section: Importantmentioning
confidence: 99%
“…The study findings indicate that green HRM affects both employee in-role and extra-role workplace green behaviour; however, this occurs through different social and psychological processes. Tsymbaliuk et al, (2021) develop a theoretical foundation for implementing environmental issues into HRM practices, including compensation and benefits, employee relations, corporate culture, communication etc. Rayner and Morgan (2018) assessed the environmental knowledge of employees and self-perceptions of ability, motivation and opportunity (AMO) to practise green behaviours by operationalizing the AMO framework towards a pro-environmental agenda.…”
Section: Literature Reviewmentioning
confidence: 99%